Bibliometric Analysis of Long Term Outcome Percutaneous Coronary Intervention VS Coronary Artery Bypass Graft for Coronary Artery Disease - Nicholas Handoyo, Christophorus; Wulansari, Yunita (Green Publisher Indonesia, 2025)
Comparison of long-term outcomes of Percutaneous Coronary Intervention (PCI) versus Coronary Artery Bypass Graft (CABG) for Coronary Heart Disease (CHD) is a crucial topic. However, the intellectual structure and thematic evolution of this literature have not been quantitatively assessed. This study conducts a bibliometric analysis to map the global research landscape, identify publication trends, key contributors, and thematic focuses. Bibliometric searches were conducted using Publish or Perish software on data from Crossref and Google Scholar. The search targeted the keyword title “Percutaneous coronary intervention VS Coronary Artery Bypass Graft” for publications from January 2020 to June 2025. After filtering and removing duplicates, 912 documents were analyzed using VOSviewer to visualize keyword co-occurrence, temporal overlays, and author collaboration. The analysis revealed “patient,” “PCI,” and “CABG” as the most dominant terms. Five thematic clusters emerged: (1) post-CABG complications; (2) PCI vs. CABG long-term outcomes; (3) stent technology and comorbidities; (4) acute conditions and mortality; and (5) complex prognostic and anatomical factors. Temporal visualization indicates a shift from broad procedural comparisons (2020–2021) to specific long-term outcome studies and population-specific research (2022 onward). Key author collaboration networks were also identified. The bibliometric landscape of PCI versus CABG research is mature yet evolving, with growing focus on patient-specific outcomes. Emerging hotspots include long-term results in subgroups and complex coronary anatomy, indicating a trend toward outcome-oriented and personalized approaches in coronary revascularization research